Methods of manufacturing photovoltaic module
Patent Information
- Application Number
- JP2024067387
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-04-16
- Filing Date
- 2024-04-18
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2039-04-12
AI Technical Summary
Existing methods for manufacturing colored photovoltaic modules are complex, require additional layers that increase the risk of delamination, and are not compatible with temperature-sensitive technologies like dye-sensitized and perovskite cells, leading to non-uniform color schemes and potential damage from conventional lamination temperatures.
A method involving a silane-modified polyolefin-based resin with a melting point below 90°C, crosslinked at lower temperatures (60°C to 125°C) to form an encapsulant, which prevents pigment migration and excessive flow, ensuring uniform color and compatibility with temperature-sensitive cells.
The method achieves uniform color schemes and mechanical stability at lower temperatures, reducing energy consumption and enabling the use of conventional equipment for manufacturing colored photovoltaic modules with temperature-sensitive technologies.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of photovoltaic devices, and more particularly to a method for manufacturing colored photovoltaic modules suitable for architectural integration applications.
[0002] Photovoltaic (PV) devices - also called solar cells or solar panels - tend to be nearly black in color, usually in shades of purple or indigo, with a clearly defined pattern of individual cells visible. When such PV devices are installed in buildings, they are an eyesore, and for this reason their direct use as building cladding is usually intolerable.
[0003] To address this issue, colored PV devices that can be integrated into the building structure, particularly as external cladding, have been proposed.
[0004] US Patent No. 5,399,633 discloses a film that is applied to the front sheet of a PV device to modify the appearance of the module, but the film requires a specific profile that must be aligned with the geometry of the individual PV cells that make up the module, and relies on a complex design that includes facets in the front sheet and embedded elements in the inactive portion of the module.
[0005] US Patent No. 5,399,633 discloses a PV device that includes a graphic film inside the module, which is printed with color or texture and requires a selectively reflective layer to limit the effect of the film on the efficiency of the module.
[0006] US Pat. Nos. 5,399,623 and 5,433,363 disclose decorative film overlays that may be provided on or within PV modules, such as US Pat. Nos. 5,499,623 and 5,433,623.
[0007] Patent Document 7 discloses a white photovoltaic module in which an interference filter is formed on an intermediate layer provided on the light-incident surface of the photovoltaic module so as to reflect a certain amount of light over the entire visible spectrum. Special equipment and methods are required to produce this interference film.
[0008] However, all of these prior art solutions are complex or require the addition of additional layers to the module, essentially increasing the risk of delamination of the module since for each additional layer added to the module there is an interface between separable layers, and may require specialized manufacturing techniques or equipment.
[0009] US 6,399,436 proposes a solution to this problem. In the embodiment of FIG. 7 of US 6,999,436 the front encapsulation layer itself contains pigment particles randomly distributed therein. This therefore does not require an additional colored film on top of the front encapsulation layer, but creates an entirely different set of problems. As the encapsulant used in US 6,999,436 is conventional and is deposited at conventional deposition temperatures of the order of 130°C to 170°C under pressures up to 1 bar, the pigment particles may migrate during deposition. This results in significant color non-uniformity. In more extreme cases, excessive encapsulant flow leads to significant thickness variations within the module, especially in areas where PV cells are present and not. This again results in color variations throughout the module.
[0010] And secondly, while standard temperatures and pressures are compatible with most PV cell technologies, such as thin-film silicon, crystalline silicon, and germanium-based cells, they are not compatible with organic and dye-sensitized cells, which are typically perovskite-based. These latter types of cells, also known as Grätzel cells, utilize a photosensitive dye adsorbed on a thin film of titanium dioxide and use a liquid or gel-based electrolyte that can be damaged if heated above 90°C. As such, these latter types of cells are not compatible with traditional deposition methods. Perovskites are similarly, though not to the same extent, sensitive to heat. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] U.S. Patent No. 9,281,186 [Patent Document 2] US Patent Application Publication No. 2014 / 326292 [Patent Document 3] U.S. Patent No. 9,276,141 [Patent Document 4] U.S. Patent No. 8,513,517 [Patent Document 5] US Patent Application Publication No. 2012 / 247541 [Patent Document 6] International Publication No. 2016 / 118885 [Patent Document 7] European Patent Publication No. 2793271 [Patent Document 8] International Publication No. 2009 / 089236 [Patent Document 9] US Patent Application Publication No. 2017 / 123122 [Patent Document 10] US Patent Application Publication No. 2017 / 033250 Summary of the Invention [Problem to be solved by the invention]
[0012] It is therefore an object of the present invention to propose a method for producing a colored photovoltaic module having a desired color scheme, and in a second aspect, a method that is compatible with dye-sensitized, perovskite and other temperature-sensitive photovoltaic technologies.
[0013] More particularly, the present invention relates to a method for manufacturing a solar cell module including at least a first layer and a second layer secured together by an encapsulant. Naturally, even if the photovoltaic module includes a photovoltaic conversion element, the photovoltaic conversion element does not have to be either the first layer or the second layer, but may be either. The method includes the steps of: providing a lamination apparatus, such as a vacuum bag lamination apparatus; providing the first layer, e.g., a front sheet, back sheet, or other layer, in the lamination apparatus, either alone or as part of an existing prefabricated PV module or PV module; providing the encapsulant, which may be applied as a sheet and / or powder, on the first layer by: (a) providing a base resin comprising a silane modified polyolefin (e.g. an ethylene containing copolymer) having a melting point below 90°C; (b) forming a mixture of said base resin and an additive comprising a crosslinking catalyst present in a ratio of 0.01 to 20, preferably 0.01 to 5 parts per 100 parts of resin, with pigment particles of any convenient type, size and concentration; (c) melting the mixture at a temperature of 90°C to 190°C, preferably 160°C to 180°C; and (d) extruding the mixture to form an encapsulant; providing the second layer, e.g., a photovoltaic conversion device, an internal front sheet forming part of an existing PV module, or other suitable layer, over the encapsulant; laminating the first layer, the second layer and the encapsulant under heat and pressure applied at a temperature of 60°C to 125°C, preferably 60°C to 100°C, and more preferably 70°C to 90°C, so as to crosslink the base resin.
[0014] During lamination at temperatures up to 125° C., at least a portion of the encapsulating resin described above may be crosslinked, resulting in suitable mechanical properties for use in PV modules, in particular sufficient stiffness and creep resistance at the highest expected application temperature (i.e. around 85° C., with a safety margin up to 105° C.). The crosslinking may also be performed or continued after the lamination of the module has been completed.
[0015] The lower than normal processing temperature results in higher than normal viscosity during lamination and a lower than normal tangent delta. This not only prevents migration and agglomeration of the pigment particles, but also prevents excess flow of the pigmented encapsulant. The result is a uniform color scheme in the module. This result is surprising and shows an unexpected synergy between the low temperature processing and the use of pigments to impart color to the module.
[0016] Moreover, this combination of specific encapsulants and lower than normal lamination temperatures is suitable for use in laminating conventional PV modules in conventional lamination equipment as well as for laminating PV modules containing temperature sensitive PV cells, such as perovskite-based cells, organic cells, or dye-sensitized cells. Lower processing temperatures during lamination also reduce energy consumption. It should be noted that one of the first and second layers described above may form part of an existing pre-fabricated PV module onto which the other layer is laminated, or may be a separate layer of the PV module.
[0017] An alternative method according to the present invention comprises: Providing a lamination device; providing said first layer (as described above) in said lamination apparatus; providing an encapsulant in powder form on said first layer, the encapsulant being realized by: (a) providing a base resin in powder form comprising a silane modified polyolefin (e.g. an ethylene containing copolymer) having a melting point below 90°C; and (b) mixing said base resin powder with at least a powder or liquid additive comprising a crosslinking catalyst present in said encapsulant (considering the entire mixture of said encapsulant) in a ratio of 0.01 to 20, preferably 0.01 to 5 parts per 100 resin, and pigment particles of convenient type, size and concentration to produce said encapsulant; providing the second layer (as described above) on the encapsulant; laminating the first layer, the second layer and the encapsulant under heat and pressure at a temperature of 60°C to 125°C, preferably 60°C to 100°C, and more preferably 70°C to 90°C, so as to crosslink the base resin.
[0018] During lamination at temperatures up to 125° C., the resin is crosslinked in the same manner as described above, even though the catalyst particles and the particles of base resin are discrete, resulting in mechanical properties suitable for use in PV modules, specifically sufficient stiffness and creep resistance at the highest expected application temperatures (i.e. around 85° C., with a safety margin up to 105° C.).
[0019] The lower than normal processing temperature results in higher than normal viscosity during lamination and a lower than normal tangent delta. This not only prevents migration and agglomeration of the pigment particles, but also prevents excess flow of the pigmented encapsulant. The result is a uniform color scheme in the module. This result is surprising and shows an unexpected synergy between the low temperature processing and the use of pigments to impart color to the module.
[0020] Thus, the method can be used to laminate conventional PV modules in conventional lamination equipment as well as to laminate PV modules containing temperature sensitive PV cells, such as perovskite-based cells or dye-sensitized cells, and the reduced processing temperature during lamination reduces energy consumption. It is noted again that one of the first and second layers described above may form part of an existing pre-fabricated PV module onto which the other layer is laminated, or may be a separate layer of the PV module.
[0021] Advantageously, the base resin has a complex viscosity at 85°C greater than 10000 Pa·s and at 100°C greater than 6000 Pa·s before lamination.
[0022] Advantageously, the base resin exhibits a tan delta value at 85°C greater than 1.0 and at 100°C greater than 1.2 prior to lamination.
[0023] The above-mentioned properties provide an encapsulant with good processability.
[0024] Advantageously, the mixture further comprises other additives including at least one of an antioxidant, an ultraviolet absorber and an ultraviolet stabilizer, which may be mixed and / or combined with the base resin simultaneously with mixing and / or combining with the catalyst or in a separate step before the resulting mixture is mixed and / or combined with the catalyst.
[0025] Advantageously, the catalyst comprises one or more of boric acid, metallocene catalysts, constrained geometry catalysts, reversible chain transfer catalysts, multi-site catalysts such as Ziegler-Natta catalysts or Phillips catalysts. Such crosslinking catalysts may comprise metal (e.g. cobalt, tin, zinc, iron, lead, etc.) carboxylic acids, dialkyltin mercaptides, tin octoate, dibutyltin dilaurate, dibutyltin diacetate, dioctyltin dilaurate, tin acetate, tin caprylate, zinc caprylate, organic bases such as ethylamine, dibutylamine, or hexylamine, inorganic acids such as sulfuric acid, or organic acids such as toluenesulfonic acid, stearic acid, and maleic acid.
[0026] Advantageously, after the lamination step, the encapsulant exhibits a complex viscosity at 85°C greater than 15000 Pa·s and at 100°C greater than 10000 Pa·s.
[0027] Advantageously, after the lamination step, the encapsulant exhibits a tan delta value of less than 1.0 at 85°C (preferably less than 0.8 at 85°C) and less than 1.2 at 100°C (preferably less than 1.0 at 85°C).
[0028] These properties are sufficient to provide the required structural stability and creep resistance at the required service temperature immediately after lamination. Further crosslinking after lamination further improves the creep resistance of the sealing layer.
[0029] Advantageously, at least a portion of the pigment particles, preferably at least 50% or even at least 75%, have a diameter with a median value in the range of 100 nm to 50 μm, preferably 100 nm to 5 μm, preferably 300 nm to 700 nm, more preferably 400 nm to 600 nm. The particle diameter can be optimized for the desired optical properties of the front sealing layer. Similarly, pigment particles may be provided in the front sealing layer in a mass concentration of 0.01 to 10 parts per 100 resin. This can again be adjusted to optimize the desired properties. It goes without saying that the exact particle size and particle concentration can be arrived at by routine experimentation to achieve the desired optical properties (color, reflectance, transmittance, special interference effects, etc.), and there is no particular a priori relationship between particle size and particle concentration, which relationship depends on the desired optical properties.
[0030] Advantageously, the pigment particles comprise at least one of a zinc-based pigment (e.g. zinc oxide or zinc chromate), a titanium-based pigment (e.g. titanium oxide or titanium yellow), an iron-based pigment (e.g. iron oxide or Prussian blue), a chromium-based pigment (e.g. chromium oxide), a bismuth-based pigment (e.g. bismuth vanadate), a cobalt-based pigment (e.g. cobalt blue) or a cobalt stannate or cobalt / lithium / titanium oxide) aluminium-based pigment (sulphur-containing sodium silicate complex), a tin-based pigment (e.g. tin sulphide) or a copper-based pigment.
[0031] Naturally, such photovoltaic modules would be suitable for use in building construction. [Brief description of the drawings]
[0032] Further details of the invention will become apparent from the following description in conjunction with the following figures. [Figure 1] FIG. 2 is a schematic cross-sectional view of a photovoltaic module manufactured according to the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of another photovoltaic module manufactured according to the present invention. [Diagram 3]1 is a schematic diagram of a method for manufacturing a photovoltaic module. [Figure 4] 1 is a schematic diagram of a method for producing an encapsulant according to the present invention. [Diagram 5] 1 is a schematic diagram of a method for producing an encapsulant according to the present invention. [Figure 6] 1 is a schematic diagram of a method for producing an encapsulant according to the present invention. [Figure 7] 1 is a schematic diagram of a method for producing an encapsulant according to the present invention. [Figure 8] 1 is a graph illustrating the environmental color stability results obtained with a PV cell according to the present invention. [Figure 9] 1 is a graph illustrating the environmental color stability results obtained with a PV cell according to the present invention. [Figure 10] 1 is a graph illustrating the environmental color stability results obtained with a PV cell according to the present invention. [Figure 11] FIG. 1 is a schematic diagram of a building structure equipped with PV modules. MODE FOR CARRYING OUT THE PRESENTINVENTION
[0033] It should be noted that hereinafter, one or more intermediate layers may also be present between the layers mentioned above, unless it is specified that a particular layer is directly disposed on an adjacent layer. Therefore, "on" should be taken to mean "directly or indirectly on" unless otherwise specified. Furthermore, the patterning of certain layers, connectors, etc. are not shown as they are well known to those skilled in the art.
[0034] FIG. 1 shows a classical construction of a photovoltaic module 1. The photovoltaic module 1 comprises a front sheet 3, which is disposed on the light-entering surface of the photovoltaic module 1 and is intended to emit light in use, and a back sheet 11, which is disposed on the surface of the module 1 opposite the front sheet 3. The front sheet 3 may be glass, transparent ceramics, polymer, or any other convenient substantially transparent material. The back sheet may be metal, glass, ceramics, polymer, or any other convenient material. The front sheet 3 may be constructed with a coating. One of the front sheet 3 and the back sheet 11 may represent the "first layer" in the present invention. The layer that this first layer seals with a sealing layer corresponds to the "second layer" in the present invention. Alternatively, any two specific layers of the construction of a PV module that are sealed together may represent the first and second layers in the present invention. Alternatively, either the first and second layers may form part of an existing pre-fabricated PV module to which the other layers are laminated.
[0035] Provided between the front sheet 3 and the back sheet 11 is a patterned and interconnected photovoltaic conversion device 7 comprising one or more PV cells having NIP, PIN, NP or PN junctions as are commonly known. The PV cells may be based on thin film silicon, crystalline silicon, germanium, perovskite, dye sensitized cells or any other type of PV technology suitable for generating electrical power from light incident on the light incident face of the PV module 1 and passing through the photovoltaic active area of the PV conversion device 7. The present invention is particularly applicable to encapsulation of PV modules incorporating dye sensitized perovskite cells, but is equally applicable to any PV cell technology.
[0036] The PV conversion device 7 is sealed on the light-incident side by a front sealing layer 5, which seals the light-incident side to the front sheet 3, and on the back side by a back sealing layer 11. The back sealing layer 11 seals the PV conversion device 15 to the back sheet 19. However, the back sealing layer 11 may itself constitute the back sheet. Each of the sealing layers 5, 9 is typically 200 μm to 1 mm thick. Furthermore, multiple front sealing layers 3 may be stacked on top of each other. The front sealing layer 5 and / or the back sealing layer 9 are specially manufactured according to the present invention. The front sealing layer 5 and / or the back sealing layer 9 are described in more detail below.
[0037] It should be noted that other intermediate layers may be provided between the layers shown, and that the layers need not be flat, but may have curvature or present more complex surfaces. In such cases, the use of a powdered encapsulant by itself or in combination with a film thereof may be advantageous in ensuring that all details of the shape are filled with the encapsulant. The same principles are applicable regardless of the shape of the layers, in particular using a powdered encapsulant to fill in certain areas on the underlying layer to ensure a uniform encapsulant layer after lamination.
[0038] FIG. 2 represents another variant of the structure of a PV module 1 manufactured by laminating a front sheet 3 to an existing pre-manufactured PV module 17 by means of a front encapsulant 5. The other layers 7, 9, 11 have been previously designed. The result is that the original front sheet and front encapsulant of the pre-manufactured module 17 are the internal front sheet 13 and the further encapsulant layer 15, respectively. The same is true for the rear encapsulant 9 and rear sheet 11. This structure allows the functionalization of the front of the existing module 17 by means of a front sheet 3 that is constructed, printed, contains the desired additives, is equipped with optical filters as disclosed, for example, in US Pat. No. 5,399,411, US Pat. No. 5,499,420, or shows a similar functionalization.
[0039] FIG. 3 illustrates diagrammatically a method for manufacturing a PV module 1 according to the invention.
[0040] A layer stack 31, comprising at least layers 3, 5, 7, 9 along with other layers present, is brought together in a lamination device 33. In the embodiment of FIG. 2, the layer stack includes a prefabricated PV module 17 onto which a front encapsulation layer 5 and a front sheet 3 (and any other desired layers) have been applied. Note that the layer stack 31 can be brought together in a lamination device 33 either with the light-incident surface of the final PV module facing up or facing down, with this orientation determining which particular layers are the "first" and "second" layers in the present invention. Furthermore, one or more of the encapsulation layers 5, 9 may be applied to the layer stack 31 as a film and / or powder.
[0041] The laminator 33 may be a vacuum bag laminator, a roller type laminator, or any other convenient type. The laminator 33 then applies heat and pressure at a lower than normal temperature, in particular 60° C. to 125° C., preferably 60° C. to 100° C., more preferably 70° C. to 90° C., and pressure up to 2 bar gauge (usually substantially 2 bar gauge) for a suitable period of time (e.g. 20 minutes to 2000 minutes), which fuses and crosslinks the various encapsulation layers into the final PV module 1.
[0042] As a result, the PV module 1 according to the present invention can be fabricated in conventional PV processing equipment without the need for special equipment, and the reduced processing temperature reduces energy consumption during manufacture.
[0043] At least one of the encapsulation layers 5, 9 is specially manufactured as described below to allow lamination at temperatures lower than the normal temperatures mentioned above while maintaining the desired mechanical properties of the encapsulation after lamination and during delivery.
[0044] The sealing layers 5, 9 in question are produced from silane-modified polyolefin-based resins, such as polyethylene or other ethylene-based polymers or copolymers or mixtures of such polymers. Such base resins contain silane functional groups already bonded to the polymer molecules and are commercially available, for example, from Padanaplast, Dow, Evonik and other companies. Hereafter, reference is made to certain specific forms with the manufacturer's reference data not varying for the specific form, so that reproducibility is guaranteed to the skilled person.
[0045] Such base resins typically comprise one or more polyolefins (e.g., polyethylene, polypropylene, or C3-C6) in the presence of a compound containing hydrolyzable silane groups. 10 Polyolefins can be obtained by processing polyolefins (copolymers of ethylene or propylene with other monomers selected from alkenes). Other examples of polyolefins are allylcyclohexane, vinylcyclohexane, norbornene, polystyrene, acrylic polymers, acrylate polymers, methacrylates, such as PMMA. Further examples of polyolefins can be consulted in ASM D883-12 or Ullman's Encyclopedia of Industrial Chemistry. The processing of the base resin may be carried out, for example, by melt processing one or more polyolefins in the presence of a compound containing hydrolyzable silane groups and a compound capable of generating free radicals. However, such base resins are available off-the-shelf from several manufacturers, so that the skilled person does not have to carry out his own synthesis, but only by choosing the appropriate base resin. The base resin in question ideally has the following properties before lamination: [Table 1]
[0046] For reference, complex viscosity is the frequency-dependent viscosity function determined during forced harmonic oscillation of shear stress and is defined as the complex modulus divided by the angular frequency. Here, the complex modulus represents the overall resistance of the material to deformation, whether that deformation is recoverable (i.e., elastic) or non-recoverable (i.e., viscous). It is measured here with a dynamic moving die rheometer or similar device at a frequency of 1 Hz and a strain of 10%. Tangent delta - also known as the "loss tangent" - is the phase angle given by the ratio of the loss modulus (G'') to the storage modulus (G') and represents the presence and magnitude of elasticity in a fluid. Again, at a frequency of 1 Hz and a strain of 10%, a tangent delta less than 1.0 suggests predominantly elastic (i.e., solid-like) behavior, while a value greater than 1 suggests predominantly viscous (i.e., liquid-like) behavior.
[0047] The density ranges cited represent an optimum in terms of crystallinity and melting point of the base resin. The melting point range ensures that the encapsulant is meltable at low lamination temperatures. The viscosity and tangent delta values are important values that reflect the processability of the encapsulant under standard lamination conditions. Examples of commercial resins with specific these properties are given in the examples below, but one skilled in the art knows how to select others based on the properties given by consulting the appropriate material data sheets. In essence, it has been shown that polymers with the above mentioned properties are laminable at the required temperatures, while those with parameters outside these ranges are typically not suitable.
[0048] The base resin is combined with a crosslinking catalyst at a concentration of 0.01 phr to 5 phr, or even up to 20 phr. The catalyst may include boric acid as a water source, a multi-site catalyst such as a metallocene catalyst, a constrained geometry catalyst, a reversible chain transfer catalyst, e.g. Ziegler-Natta catalyst or Phillips catalyst, or any other type of catalyst suitable for catalyzing the crosslinking of polyolefin molecules with silanes and water. The water may be ambient water and / or may be provided by, e.g., boric acid or a similar compound that decomposes to release water when heated. The catalyst may be provided as a powder or solution, or may already be incorporated with the polymer in a catalyst masterbatch. Other examples of such catalysts are metal (e.g., cobalt, tin, zinc, iron, lead, etc.) carboxylic acids, dialkyltin mercaptides, stannous octoate, dibutyltin dilaurate, dibutyltin diacetate, dioctyltin dilaurate, stannous acetate, stannous caprylate, zinc caprylate, organic bases such as ethylamine, dibutylamine, or hexylamine, inorganic acids such as sulfuric acid, or organic acids such as toluenesulfonic acid, stearic acid, and maleic acid.
[0049] Hereafter, the preparation of such catalysts is again referred to by the manufacturer's reference data, which do not vary for the specific form, so that reproducibility is guaranteed to the skilled person.
[0050] Other additives, such as antioxidants, UV absorbers, and / or UV stabilizers, may be added to the encapsulant base resin at a concentration of, for example, 0.1% to 5%. The encapsulant further comprises pigment particles as further additives. Such particles may be present at a concentration of, for example, 0.01 to 10 phr or wt%, preferably 0.1 to 5 phr or wt%, more preferably 0.1 to 1 phr or wt%, and may have a size ranging from 100 nm to 1 μm, more preferably 300 nm to 700 nm, and most preferably 400 nm to 600 nm. Preferably, at least 50%, more preferably at least 75%, and more preferably substantially all of the pigment particles have a set size. It should be noted that the pigment particles are distinct discrete particles from encapsulants made of colorants or already colored materials dispersed at a molecular level within the encapsulant. As an example of a suitable pigment, titanium oxide or zinc oxide particles may be used to produce a white color. Yellow, orange, red, and brown can be produced using iron oxides—Fe2O3 for red-brown or FeO(OH) for yellow. Blue can be produced, for example, with sulfur-containing sodium silicate complexes or Prussian blue. Such pigment particles 21 absorb a portion of the visible light incident on the PV device 1 to produce the desired color, and diffuse the light to provide a uniform color and hide various features of the PV conversion device 15, such as the patterning of the PV conversion device 15, the electrical interconnects between the individual cells, the edges of the individual cells, and color misalignment between the individual cells and the back encapsulant 17 and / or backsheet 19.
[0051] More detailed examples of specific off-the-shelf pigments that have been tried successfully are as follows: · Red: Iron oxide red pigments - e.g. Rot 110M from Scholz Farbpigmente Schweiz, Switzerland, Sicocer® F Coral 2320 from BASF. Typical dosages are 0.05-2 phr. · White: Dupont Ti-Pure R-900, R-960 from Dupont. Typical dosages are 0.1-1 phr. · Yellow: Nubifer Y-4000 from Ferro. Typical dosages are 0.1-2 phr. · Green: PG17 S series from Ferro, Sicopal® GREEN K 9610 or 9710 from BASF. Typical dosages are 0.05-2 phr.
[0052] Of course, other commercially available pigment particles are also mentioned, including zinc-based pigments (e.g. zinc oxide or zinc chromate), titanium-based pigments (e.g. titanium oxide or titanium yellow), iron-based pigments (e.g. iron oxide or Prussian blue), chromium-based pigments (e.g. chromium oxide), bismuth-based pigments (e.g. bismuth vanadate), cobalt-based pigments (e.g. cobalt blue) or cobalt stannate or cobalt / lithium / titanium oxide) aluminum-based, pigments (sulfur-containing sodium silicate complexes), tin-based pigments (e.g. tin sulfide) or copper-based pigments.
[0053] The pigment particles 21 absorb a portion of the visible light incident on the PV device 1 to produce a desired color, and also diffuse the light to provide a uniform color and hide various features of the PV conversion device 15, such as the patterning of the PV conversion device 15, the electrical interconnections between the individual cells, the edges of the individual cells, and color misalignment between the individual cells and the back encapsulant 17 and / or backsheet 19.
[0054] This scattering effect is particularly advantageous over simply providing a front encapsulant that is colored with a colorant dispersed therein at the molecular level, because such a colorant would hide the various features of the PV conversion elements 7 mentioned above, without the light scattering resulting in much greater optical transparency.
[0055] Additionally, the scattering effect facilitates diffusion of light passing through the front encapsulant 5 and incident on the photoelectrically active portion of the PV conversion element 7 in a manner similar to that of a conventional diffusing element included within the PV module 1 on the light incident face of the PV conversion element 7, thereby increasing the average optical path length of the light passing through the cell. Naturally, the overall efficiency is reduced in proportion to the light that is reflected or scattered back towards the light incident face of the PV device.
[0056] The size of the pigment particles 21 can be adjusted to increase the transmittance in the infrared range of the IR light sensitive PV conversion element 5. By optimizing the size and density of the pigment particles in the front encapsulation layer 5, interference between the pigment particles 21 can be created that gives a sparkle, glimmer, or rainbow effect. More specifically, the size and concentration of the pigment particles, the front encapsulation layer, etc. can be adjusted by routine experimentation within the above ranges to achieve the desired color, optical effect, transmittance, reflectance, etc.
[0057] The mixture of base resin, pigment particles, and catalyst (plus any other additives) may be combined and then extruded, for example by a twin screw extruder or other form of extruder, at a temperature between 90°C and 190°C, preferably at a temperature between 140°C and 180°C, preferably at a temperature between 160°C and 180°C, preferably at a temperature between 165°C and 180°C, to produce an encapsulant film or any other convenient form (e.g. cylinder) that is later ground into a powder. This is represented diagrammatically in Figure 4, where the base resin and catalyst preparation (including catalyst powder, solution, or catalyst masterbatch containing catalyst already combined with the polymer) are mixed, combined, and extruded. Figure 5 represents diagrammatically another variation of this process, where the base resin is mixed and combined with other additives, such as UV absorbers, UV stabilizers, and / or antioxidants, and then extruded. The resulting mixture is then mixed and compounded with the catalyst preparation (described above) and extruded.
[0058] Conventional extrusion processes ensure that cross-linking of the polymer is relatively unlikely, due to the relatively short residence time of the melt in the extruder before solidifying. However, some will occur and is not problematic. If excessive cross-linking does occur in the extruder, one skilled in the art can easily modify the extrusion parameters (temperature, extrusion pressure, extrusion flow rate, etc.) by routine experimentation to resolve such issues. The sheets and / or powders may then be provided in a layer stack 31 in a lamination device 33 as described above. With the application of heat and pressure, the silane cross-links the polymer molecules in the presence of water (which may come, for example, from boric acid or other components of the catalyst) at the lamination temperature, thereby curing the sealing material and bonding it to adjacent layers.
[0059] In another variant, the base resin and any additives other than the catalyst are combined at the above mentioned temperature, extruded into a shape such as a cylinder or strand, and then ground to a powder. As shown diagrammatically in FIG. 6, this base resin powder may then be mixed with a crosslinker powder or liquid (by itself or already combined with the polymer) containing a crosslinker (i.e. catalyst) material, pigment particles, and optionally further additives - antioxidants, UV absorbers, and / or UV stabilizers. This powder may have a particle size of 1-1000 μm, preferably 1-100 μm. The resulting powder mixture constitutes the encapsulant of the invention. In a further variant of this process, shown diagrammatically in FIG. 7, the base resin (which may be in the form of a powder, pellets, or any other convenient form) and the above mentioned further additives are first mixed, combined, and extruded. The resulting mixture is then ground to a powder. This latter powder is then mixed with the crosslinker described above in powder or liquid form (which may or may not contain a polymeric component) to form the encapsulant powder.
[0060] This powder mixture is then placed into the layer stack 31 described above and heat is applied at 60°C to 125°C, preferably 60°C to 100°C, more preferably 70°C to 90°C, and pressure of 0.5 to 2 bar gauge, causing the catalyst to interact with the base resin as the components soften and bond, thereby crosslinking the polymers of the base resin in the same way as if the catalyst were mixed into the base resin prior to extrusion.
[0061] After lamination, the resulting encapsulant has the following modified properties, which when applied provide the desired strength and creep resistance: [Table 2]
[0062] As a result, the rheological behavior of the encapsulant during the entire process is controlled. As a result, migration of pigment particles and excess material during lamination is prevented. Agglomeration of pigment particles and significant flow of the encapsulant are avoided. As a result, the coloration of the module is uniform. The reason for this is that the viscosity of the encapsulant remains high during the entire process (at a complex viscosity of ≧4000 Pa·s, the tangent delta value of the encapsulant remains below 1.2, preferably below 1.0), which prevents migration of the pigment particles, especially during the early stages of lamination when heat is applied. During this stage of conventional lamination, the viscosity value is typically relatively low before it is time for the encapsulant to cure, thereby allowing migration and agglomeration of pigments and excess material flow, which would result in significant thickness variations of the encapsulant layer. This synergistic effect, especially between low-temperature lamination and avoidance of pigment migration and excess material flow, allows a very uniform coloration of the module, giving an unexpected technological effect.
[0063] A number of test results without pigment are reproduced below. The following test results provide specific examples of specific combinations of materials that allow the method of the present invention to achieve the desired results of good low temperature lamination and achieve the desired mechanical and rheological properties of the sealing layer.
[0064] "Example 1" [Table 3]
[0065] Table 3 details the formulation of this example, where "phr" refers to parts per 100 resin. The antioxidants and UV stabilizers were first compounded into an additive masterbatch by a twin screw extruder at 170°C. The mixture of base resin, catalyst masterbatch and additive masterbatch was then extruded into a film with a thickness of 0.5 mm by a single screw extruder at 170°C. The extruded film was then tested in a series of evaluation steps.
[0066] The film was first laminated between two glass plates, each 3 mm thick, in a standard flatbed vacuum bag laminator at 65°C with a total cycle time of 60 minutes. The resulting laminate was free of air bubbles and other visual defects. The post-lamination peel strength between the foil and glass was measured to be greater than 10 N / mm by a standard 90° peel test performed with a standard tensile testing apparatus. The laminated glass plates were then subjected to a standard creep test at 85°C and 85% relative humidity. The results showed that no creep had occurred under the weight of the glass even after 100 hours, which was 15 kg / m 2 is equivalent to a stack of
[0067] "Example 2" [Table 4]
[0068] Table 4 details the formulation of this example. The antioxidants, UV absorbers, and UV stabilizers were first compounded into an additive masterbatch in a twin screw extruder at 170° C. The mixture of base resin (containing a 50:50 mixture of two different resins shown in the table), catalyst masterbatch, and additive masterbatch was then extruded into a 0.5 mm thick film in a single screw extruder at 170° C. The extruded film was then tested in a series of evaluation steps.
[0069] The film was first laminated between two glass plates, each 3 mm thick, in a standard flatbed vacuum bag laminator at 85°C with a total cycle time of 60 minutes. The resulting laminate was free of air bubbles or other visual defects. The post-lamination peel strength between the foil and glass was measured to be greater than 5 N / mm using the standard 90° peel test described above. The laminated glass plates were then subjected to a standard creep test at 85°C and 85% relative humidity. The results showed no creep, even after 100 hours. Example 3 [Table 5]
[0070] Table 5 details the formulation of this example. The antioxidant, UV absorber, and UV stabilizer were first compounded into an additive masterbatch by a twin screw extruder at 170° C. The mixture of base resin, catalyst masterbatch, and additive masterbatch was then extruded into a 0.5 mm thick film by a single screw extruder at 170° C. The extruded film was then tested in a series of evaluation steps.
[0071] The film was first laminated between two glass plates, each 3 mm thick, in a standard flatbed vacuum bag laminator at 85°C with a total cycle time of 60 minutes. The resulting laminate was free of air bubbles and other visual defects. The post-lamination peel strength between the foil and glass was measured to be greater than 5 N / mm by the standard 90° peel test described above. The laminated glass plates were then subjected to a standard creep test at 85°C and 85% relative humidity. The results showed no creep, even after 100 hours.
[0072] "Example 4" [Table 6]
[0073] Table 6 details the formulation of this example. The antioxidants and UV stabilizers were first compounded into an additive masterbatch by a twin screw extruder at 190° C. The mixture of base resin, catalyst masterbatch and additive masterbatch was then extruded into a 0.5 mm thick film by a single screw extruder at 170° C. The extruded film was then tested in a series of evaluation steps.
[0074] The foil film was first laminated between two glass plates, each 3 mm thick, in a standard flatbed vacuum bag laminator at 85°C with a total cycle time of 60 minutes. The resulting laminate was free of air bubbles or other visual defects. The post-lamination peel strength between the foil and glass was measured to be greater than 10 N / mm by the standard 90° peel test described above. The laminated glass plates were then subjected to a standard creep test at 85°C and 85% relative humidity. The results showed no creep after 100 hours.
[0075] As the above results show, the encapsulant produced by the method of the present invention can be laminated at significantly lower temperatures than conventional methods while maintaining peel strength and creep resistance at 85° C. As a result, conventional lamination equipment and methods can be used to fabricate PV modules containing temperature sensitive PV cells, such as those based on perovskite or dye-sensitized technology.
[0076] Regarding the use of dyes, the presence of the dyes did not affect the mechanical properties of the resulting modules. Furthermore, during annealing, the colored encapsulants did not undergo any bleaching or change in properties. As a result, it can be concluded that no specific cross-degradation mechanism occurred between the dyes and the encapsulants used.
[0077] The results of chemical and UV stability tests of various samples produced according to the present invention are reported in Figures 8-10 as follows.
[0078] Figure 8 shows a graph of reflectance and transmittance versus wavelength for various equivalent exposure times in a standard QSun exposure chamber. In the graph, a module was constructed according to Figure 1, using a 0.8 mm thick polyolefin type front encapsulant 21 (Polidiemme FE1252 EXP) containing 1 phr of TiO2 pigment (DuPont Ti-Pure R-960, median particle size: 0.5 μm). The front sheet was a glass plate with a thickness of 2 mm. As can be seen, there was no change in reflectance or transmittance for exposures equivalent to up to 6423 hours of sunlight at any wavelength of light. The changes were simply within the measurement variability.
[0079] The perceived color change was also measured according to the CIE (1994) standard. [Table 7]
[0080] As can be seen from the figure, ΔE CIE94 The values of are very low and remain virtually constant (within the measurement variability) over long exposure times. In a practical sense, no color shifts were observed.
[0081] Figure 9 shows the sample from Figure 8 subjected to 1000 hours of decaying thermal exposure per IEC 61215 at 85°C and 85% relative humidity. Again, little difference was observed in transmittance and reflectance at any wavelength, with a ΔE of 0.62 at 1000 hours. CIE94 Values of 0.001 and 0.001 were obtained, and again, in a practical sense, no color change was observed.
[0082] Figure 10 shows the same red dyed sample used to generate the data in Figure 8, except that the dye was iron oxide (Scholz Farbpigmente Rot 110M with a median particle size of 0.5 μm) at a concentration of 0.1 phr, which gave similar results as before. ΔE CIE94 The values were as follows: [Table 8]
[0083] So again, in a practical sense, no color change was observed.
[0084] Finally, Fig. 11 represents a photovoltaic module 1 according to the invention mounted on the ceiling of a building structure 35. Alternatively, the PV module 1 may be mounted on an external wall or integrated into the wall and / or ceiling structure - for example as a cladding. In a general sense, the PV module 1 may be mounted on or inside the building structure 35.
[0085] Although the present invention has been described in specific embodiments, variations of the invention are possible without departing from the spirit and scope of the invention as defined in the claims.
Claims
1. 1. A method for manufacturing a photovoltaic module comprising at least a first layer and a second layer secured together by an encapsulant, comprising: Providing a lamination device; providing the first layer in the lamination apparatus; providing an encapsulant on the first layer by providing a base resin having a melting point below 90°C comprising a silane modified polyolefin; forming a mixture of said base resin, pigment particles and an additive comprising a crosslinking catalyst present in a ratio of 0.01 to 20 parts per 100 parts of resin; melting said mixture at a temperature of 90°C to 190°C; and extruding said mixture to form an encapsulant; providing the second layer over the encapsulant; laminating the first layer, the second layer, and the encapsulant under heat and pressure applied at a temperature of 60° C. to 125° C. to crosslink the base resin; The base resin has a complex viscosity of greater than 10,000 Pa·s at 85° C. and greater than 6,000 Pa·s at 100° C. before lamination; said base resin exhibiting a tan delta value at 85°C less than 1.0 and at 100°C less than 1.2 prior to lamination; After the lamination step, the encapsulant exhibits a complex viscosity at 85° C. of greater than 15,000 Pa·s and at 100° C. of greater than 10,000 Pa·s; After the lamination step, the encapsulant exhibits a tan delta value of less than 1.0 at 85° C. and less than 1.2 at 100° C. method.
2. The method of claim 1 , wherein the encapsulant is extruded as a sheet.
3. The method of claim 1 , wherein the encapsulant is extruded and subsequently ground into a powder before being disposed over the first layer.
4. 1. A method for manufacturing a photovoltaic module comprising at least a first layer and a second layer secured together by an encapsulant, comprising: Providing a lamination device; providing the first layer in the lamination apparatus; providing an encapsulant in powder form on the first layer, the encapsulant being realized by providing a base resin in powder form, the base resin having a melting point of less than 90° C., the base resin comprising a silane-modified polyolefin; and mixing an additive comprising a crosslinking catalyst present in the encapsulant in a ratio of 0.01 to 5 parts per 100 parts of resin, pigment particles, and the powder of the base resin to form a mixture to form the encapsulant; providing the second layer over the encapsulant; laminating the first layer, the second layer, and the encapsulant under heat and pressure at a temperature of 60° C. to 125° C. to crosslink the base resin; The base resin has a complex viscosity of greater than 10,000 Pa·s at 85° C. and greater than 6,000 Pa·s at 100° C. before lamination; said base resin exhibiting a tan delta value at 85°C less than 1.0 and at 100°C less than 1.2 prior to lamination; After the lamination step, the encapsulant exhibits a complex viscosity at 85° C. of greater than 15,000 Pa·s and at 100° C. of greater than 10,000 Pa·s; After the lamination step, the encapsulant exhibits a tan delta value of less than 1.0 at 85° C. and less than 1.2 at 100° C. method.
5. 5. The method of claim 1, wherein the mixture further comprises other additives including at least one of an antioxidant, an ultraviolet absorber, and an ultraviolet stabilizer.
6. 6. The method of claim 5, wherein the catalyst comprises one or more of boric acid, a metallocene catalyst, a constrained geometry catalyst, a chain shuttling catalyst, a multi-site catalyst such as a Ziegler-Natta catalyst or a Phillips catalyst.
7. The method of claim 6 , wherein at least a portion of the pigment particles have a diameter in the range of 100 nm to 50 μm.
8. The method of claim 7 , wherein the pigment particles are provided in the encapsulant at a weight concentration ranging from 0.01 to 10 parts per 100 parts of resin.
9. 9. The method of claim 8, wherein the pigment particles comprise at least one of a zinc-based pigment, a titanium-based pigment, an iron-based pigment, a chromium-based pigment, a bismuth-based pigment, a cobalt-based pigment, an aluminum-based pigment, a tin-based pigment, and a copper-based pigment.